Revitalization of Social Capital, Supply-Demand & Food Supply Chain as Strategic Assets in Entrepreneurial Development in Border Areas - Usman Usman; Siprianus Jewarut; Maria Siokalang; Veneranda Rini Hapsari; Kusnanto Kusnanto (Journal of Research in Social Science and Humanities, 2025)
Bengkayang as a border area often faces structural challenges in various sectors of economic development and infrastructure, especially in the food entrepreneurship sector. This research aims to analyze the role and revitalization of social capital as  a strategic asset in developing food entrepreneurship in border areas. However, the potential of local entrepreneurship can be developed through the revitalization of social capital, the optimization of supply-demand mechanisms, and the strengthening of the food supply chain. This research aims to examine how these three elements can synergize as strategic assets in encouraging entrepreneurial growth in border areas, especially in Bengkayang Regency, West Kalimantan. The research method uses a qualitative approach with case studies and data collection techniques through in-depth interviews, participatory observation, and document analysis. The results of the study show that the revitalization of social capital can increase access to market information, facilitate collaboration between business actors, and strengthen local institutions. The conclusion of this study confirms that the integration between social capital and an adaptive food supply chain system is able to create a sustainable entrepreneurial ecosystem in border areas.